Carbon dioxide capture at various temperatures using Ca(OH)2 sorbent fabricated by sol-gel route in ethanol media - Mohd Daud, Farah Diana; Sreekantan, Srimala; Mohamed, Abdul Rahman (Trans Tech Publications Ltd., 2014)
Carbon dioxide (CO2) is considered to be the main greenhouse gas contributing to global warming and climate change. Therefore, the present paper investigates the CO2-capture performance of synthesized calcium hydroxides, Ca(OH)2 sorbent at different temperatures which are 350, 450, 550 and 650ºC. The CO2 adsorption of the materials synthesized was studied in a thermo-gravimetric analyzer (TGA). The CO2 adsorption temperature strongly influenced the capture performance of the absorbent. The Ca(OH)2 sorbent are prepared by hydrolysis of calcium alkoxides, NaOH as precipitating agent and mixed solvent of ethanol with deionized (DI) water as medium at 35ºC. Xray diffraction (XRD) result showed 40 nm crystallite size of Ca(OH)2 hexagonal crystal structures. The Ca(OH)2 particle size and morphological properties before and after CO2 adsorption are studied by Field Emission Scanning Electron Microscopy (FESEM). The FESEM image indeed showed the rod like shape of Ca(OH)2 structures with rod length increased from 765 to 893 nm while the diameter is between 140 to 160 nm. When Ca(OH)2 sorbent adsorbed CO2, the structures are rigid interconnected each others like a lump shaped. The prepared Ca(OH)2 sorbent possesses a great potential to capture CO2 when increased temperature. Nevertheless, at intermediate temperatures (350-450ºC), Ca(OH)2 sorbent still demonstrates a higher CO2 capture capacity than other intermediate temperature adsorbents such as layered double hydroxides (LDHs), lithium zirconates (LiZrO3) and hydrotalcites.